1988
DOI: 10.1148/radiology.166.3.3340775
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation: imaging with Tc-99m HMPAO-labeled leukocytes.

Abstract: Leukocytes labeled with technetium-99m hexamethylpropyleneamine oxime (HMPAO) were used in 100 patients: 32 with suspected inflammatory bowel disease, 17 with fever of unknown origin, 21 with suspected abdominal sepsis, 20 with suspected bone sepsis, seven with bronchiectasis, and three with recent myocardial infarction. The distribution of activity in patients subsequently shown not to have inflammatory bowel disease was similar to that previously described for indium-111-labeled leukocytes. However, in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
6

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(52 citation statements)
references
References 0 publications
4
42
0
6
Order By: Relevance
“…Our results confirm the high accuracy of 99mTc-WBC scans (96%) for the diagnosis of IBD, as previously reported [16][17][18][19][20]. lllIn-lgG scanning does not seem to be as accurate (sensitivity: 70%; accuracy: 74%) in diagnosing IBD (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirm the high accuracy of 99mTc-WBC scans (96%) for the diagnosis of IBD, as previously reported [16][17][18][19][20]. lllIn-lgG scanning does not seem to be as accurate (sensitivity: 70%; accuracy: 74%) in diagnosing IBD (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…The radiation-absorbed estimates for 99m Tc-HMPAOlabeled monocytes, compared with stabilized 99m Tc-HMPAO-labeled WBCs (14), were a fraction higher but comparable with 99m Tc-HMPAO-labeled granulocytes (19) and the effective dose published in ICRP Publication 62 (20).…”
Section: Discussionmentioning
confidence: 62%
“…32 Nonspecific bowel activity, unrelated to inflammatory bowel disease, has in other studies been observed in the small bowel and proximal colon as early as 30 minutes after injection of technetium-99m exametazime-labeled cells 33 and been found in about 15% of subjects within the first hour. 29,34 In other series, such activity has first been seen on 2-hour images in 7% or on 3-4-hour images in 5%-28% of examinations 31,[35][36][37] or to occur only later than 3 hours. 38 We applied neither fasting conditions before scanning 39 nor injection of pethidine before the reinjection of labeled cells, 40 which has been shown to increase the frequency of gall bladder visualization from 10% to 44% and from 29% to 72%, respectively.…”
Section: Discussionmentioning
confidence: 99%